The Eighty-Sixth General Meeting of the Archaeological Institute of America - Anonymus, A.
329f.: R. Ellis, Early Near Eastern Textile Industries; 333: E. F. Henrickson, Houses or Temples? ’Ubaid Tripartite Architecture in Mesopotamia; 338: N. W. Leinwand, Archaeological Evidence for Hittite Cult Statuary; 351: G. S. Schwartz, Relations between Syria, Mesopotamia, and the Upper Euphrates in the Fourth-Third Millennium B.C.: The Ceramic Evidence.